Pengalaman keluarga merawat penderita pasca stroke di kota Jambi tahun 2019 - Kadarwati Kadarwati; Rahmi Ulfa; Elvi Oktarina (Berita Kedokteran Masyarakat (BKM), 2019)
Family experience for the first time caring for post-stroke sufferers at homePurpose: Neurological deficits of post-stroke patients have a negative impact on patients and families. To explore in-depth the experiences of families caring for post-stroke sufferers.  Method: Qualitative research method using a descriptive phenomenology approach. Data of nine participants selected using purposive sampling. Data collected by interviews in-depth semi-structured duration of 60-90 minutes. Data analysis using the Colaizzi method.Results: This study found five themes: dependence on daily activities in the family, efforts made by the family to fulfill self-care activities, constraints faced by caregivers, family expectations and limited knowledge and skills of caregivers. Conclusion: Families experienced difficulties in meeting patients' ADLs. They have major changes in physical conditions, rest and sleep pattern, psychological conditions, social activities, and income opportunities. The families are in need of help from others and about how to treat post-stroke patients at home.